Capture of microtubule plus-ends at the actin cortex promotes axophilic neuronal migration by enhancing microtubule tension in the leading process - Hutchins, B. Ian; Wray, Susan (Frontiers in Cellular Neuroscience, 2014)
Microtubules are a critical part of neuronal polarity and leading process extension, thus microtubule movement plays an important role in neuronal migration. However, the dynamics of microtubules during the forward movement of the nucleus into the leading process (nucleokinesis) is unclear and may be dependent on the cell type and mode of migration used. In particular, little is known about cytoskeletal changes during axophilic migration, commonly used in anteroposterior neuronal migration. We recently showed that leading process actin flow in migrating GnRH neurons is controlled by a signaling cascade involving IP3 receptors, CaMKK, AMPK and RhoA. In the present study, microtubule dynamics were examined in GnRH neurons. Failure of the migration of these cells leads to the neuroendocrine disorder Kallmann Syndrome. Microtubules translocated forward along the leading process shaft during migration, but reversed direction and moved toward the nucleus when migration stalled. Blocking calcium release through IP3 receptors halted migration and induced the same reversal of microtubule translocation, while blocking cortical actin flow prevented microtubules from translocating toward the distal leading process. Super-resolution imaging revealed that microtubule plus-end tips are captured at the actin cortex through calcium-dependent mechanisms. This work shows that cortical actin flow draws the microtubule network forward through calcium-dependent capture in order to promote nucleokinesis, revealing a novel mechanism engaged by migrating neurons to facilitate movement.